Answer :

We have been given that,

And we have to solve for .

We know the formula: (x + y)(x – y) = x^{2} – y^{2}

Using this,

Also, we know the relationship between cos θ and sin θ which is given by

cos^{2} θ + sin^{2} θ = 1

⇒ cos^{2} θ = 1 – sin^{2} θ

So,

⇒

As we know,

So, B = 7 and P = 8

By Pythagoras theorem,

H^{2} = P^{2} + B^{2}

H^{2} = 8^{2} + 7^{2}

= 64 + 49

=113

H = √113

As we know,

So,

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Given <span lang=AP- Mathematics

If 3 tanA = 4, thAP- Mathematics

In a right angle AP- Mathematics

In a right angle AP- Mathematics

In a right angle AP- Mathematics

Evaluate the follAP- Mathematics

Evaluate the follAP- Mathematics

If <span lang="ENAP- Mathematics

If <a name="MTBlaAP- Mathematics

The sides of a riAP- Mathematics